Desire for childbearing in the view of Iranian parents: A qualitative study - Maryam Mesbah; Sulmaz Ghahramani; Reza Amani; Elham Rahmanipour; Mohammad Ghorbani; Ahmad Kalateh Sadati; Sara Sadeghieh; Kamran Bagheri Lankarani (PLoS ONE, 2025)
Background and Aims Like many other countries, Iran is facing a declining population growth rate. While previous research has primarily focused on childless individuals or parents of only one child, limited attention has been paid to families who, despite already having two or more children, continue to desire larger families. This study examines childbearing motivations among Iranian parents with two or more planned children. Methods This explorative qualitative study was conducted in 2023 across three provinces in Iran. A total of 46 participants were purposively selected. Data were collected through semi-structured interviews, and thematic analysis was used to identify core themes related to childbearing motivations. Results Participants’ desire to have more children was shaped by six major themes: family altruism, value–attitude motivation, real happiness, resilience development, institutional support, and multifaceted balance. These themes reflect a dynamic interplay of emotional, cultural, and practical considerations in shaping fertility intentions. Conclusion The findings indicate that both personal and societal factors contribute to parents’ motivation for having more children. Institutional support also emerged as an important influence in the decision to pursue larger families. Understanding these motivations can inform policies aimed at encouraging childbearing among younger generations and help guide the development of integrated strategies and educational initiatives. Future quantitative research is recommended to assess the relative importance of each identified theme.